The heat shock factor GhHSFA4a positively regulates cotton resistance to Verticillium dahliae - Liu, Lu; Wang, Di; Zhang, Chao; Liu, Haiyang; Guo, Huiming; Cheng, Hongmei; Liu, Enliang; Su, Xiaofeng (Frontiers in Plant Science, 2022)
Heat shock factors (HSFs) play a crucial role in the environmental stress responses of many plant species, including defense responses to pathogens, but their role in cotton resistance to Verticillium dahliae is unclear. We previously identified numerous differentially expressed genes (DEGs) in Arabidopsis thaliana after inoculation with V. dahliae. Here, we found that GhHSFA4a in Gossypium hirsutum (cotton) after inoculation with V. dahliae shares high identity with a DEG in A. thaliana in response to V. dahliae infection. Quantitative real-time PCR (qRT-PCR) analysis indicated that expression of GhHSFA4a was rapidly induced by V. dahliae and ubiquitous in cotton roots, stems and leaves. In a localization analysis using transient expression, GhHSFA4a was localized in the nucleus. Virus-induced gene silencing (VIGS) revealed that downregulation of GhHSFA4a significantly increased susceptibility of cotton to V. dahliae. To investigate GhHSFA4a-mediated defense, 814 DEGs were identified between GhHSFA4a-silenced plants and controls by comparatively RNA-seq analysis. Kyoto encyclopedia of genes and genomes (KEGG) analysis showed that DEGs were enriched in “flavonoid biosynthesis”, “sesquiterpenoid and triterpenoid biosynthesis”, “linoleic acid metabolism” and “alpha-linolenic acid metabolism”. The expression of marker genes for the four pathways was triggered after inoculation with V. dahliae. Moreover, GhHSFA4a-overexpressing lines of A. thaliana enhanced resistance against V. dahliae, compared with the wild type. The results indicate that GhHSFA4a is involved in the synthesis of secondary metabolites and in signal transduction, which is indispensable for innate immunity in cotton to V. dahliae.